Significance of Invitro Isolation of Alternaria alternata from Onychomycotic Patients - Farwa, Umme; Farooq, Wajiha; Saeed, Asim; Hussain, Shagufta (International Journal of Pathology, 2018)
Objectives: To determine the isolation rate of Alternaria alternata in patients with clinical OnychomycosisStudy Design: Descriptive (cross sectional) studyPlace and Period of Study: Department of Microbiology, Armed Forces Institute of Pathology Rawalpindi, from August2011-April 2012.Material and Methods: Sample size; 200 nail samples, Sampling Technique; Non probability convenience sampling.Nail clippings and nail scrapings were obtained from affected nails of patients clinically having onychomycosis. Directmicroscopic examination with 30% potassium hydroxide mounts and culture on Sabouraud’s dextrose agar (SDA), SDAcontaining Chloramphenicol, and SDA containing actidione and chloramphenicol were used for species identification.Results: Out of 200 nail specimens, 94 (47%) yielded positive fungal growth, while 106 (53%) nail specimens were foundnegative on culture.Non-dermatophyte moulds (NDMs) accounted for 62 (66%) of total culture positive cases, out of which Alternariaalternata was the commonest species (29%).Dermatophytes were isolated from 20 (21%) all belonging to genus Trichophyton spp. and 12 (13%) were yeast.Conclusion: Study has yielded high number of NDMs especially Alternaria alternata, hence large scale multicentreclinical studies are required to ascertain the clinical significance of Alternaria alternata as pathogen particularly inpatients with immunosuppression, as a causative agent of onychomycosis. Moreover, clinical trials to see the treatmentoutcome of NDMs isolated from these patients, will further help to unfold the clinical significance of this study.